2019
DOI: 10.1029/2018jb017253
|View full text |Cite
|
Sign up to set email alerts
|

Brittle‐Ductile Deformation and Tensile Rupture of Dome Lava During Inflation at Santiaguito, Guatemala

Abstract: Gas-and-ash explosions at the Santiaguito dome complex, Guatemala, commonly occur through arcuate fractures, following a 5-to 6-min period of inflation observed in long-period seismic signals. Observation of active faults across the dome suggests a strong shear component, but as fault propagation generally proceeds through the coalescence of tensile fractures, we surmise that explosive eruptions require tensile rupture. Here, we assess the effects of temperature and strain rate on fracture propagation and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 111 publications
(179 reference statements)
3
23
0
Order By: Relevance
“…6, Table 4), as has been noted for other volcanic rocks; cold (e.g. Harnett et al, 2019a), hot (Hornby et al, 2019) and fragmented by pore overpressure (Spieler et al, 2004). The average UTS of each group of dry samples revealed that the strongest was UNZ9b (3.39 MPa), the cataclastic sample cored perpendicular to the cataclastic fabric (and fractured in tension parallel to fabric) and weakest was UNZ9a (1.80 MPa), the cataclastic sample cored parallel to the fabric (thus fractured in tension perpendicular) despite having equivalent porosities.…”
Section: Relationships Between Physical and Mechanical Attributessupporting
confidence: 65%
See 2 more Smart Citations
“…6, Table 4), as has been noted for other volcanic rocks; cold (e.g. Harnett et al, 2019a), hot (Hornby et al, 2019) and fragmented by pore overpressure (Spieler et al, 2004). The average UTS of each group of dry samples revealed that the strongest was UNZ9b (3.39 MPa), the cataclastic sample cored perpendicular to the cataclastic fabric (and fractured in tension parallel to fabric) and weakest was UNZ9a (1.80 MPa), the cataclastic sample cored parallel to the fabric (thus fractured in tension perpendicular) despite having equivalent porosities.…”
Section: Relationships Between Physical and Mechanical Attributessupporting
confidence: 65%
“…Volcanic rock strength inversely correlates with porosity, and is frequently defined in terms of uniaxial compressive strength (UCS) at room or high temperature (e.g. Heap et al, 2014b, c;Schaefer et al, 2015;Coats et al, 2018;Bubeck et al, 2017;Pappalardo et al, 2017), direct and indirect tensile strength at room or high temperature (Harnett et al, 2019a;Lamur et al, 2018;Hornby et al, 2019;Lamb et al, 2017;Benson et al, 2012) and triaxial tests at varying pressures, temperatures and saturation conditions (Heap et al, 2016a;Smith et al, 2011;Farquharson et al, 2016;Shimada, 1986;Kennedy et al, 2009;Mordensky et al, 2019). Strength of volcanic rocks also typically positively correlates with strain rate (Schaefer et al, 2015;Coats et al, 2018), which in combination with variability in pore geometry, crystallinity and other textural parameters of volcanic rocks ensures that scatter in volcanic rock strength is high (Lavallée and Kendrick, 2020;Heap et al, 2016b).…”
Section: Rock Failure and Volcano Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant strengths measured in all test types display a porosity control, irrespective of the stress field experienced (Figure 7(a)), which follows the common porosity-strength trend (Figures 7(b) and 7(c)) for a range of igneous rock types, regardless of TT [7,11,63,87,88]. The treatment temperature has a strong impact on porosity (Figure 4(c)), thereby further influencing mechanical compaction; however, comparison with strength and Young's modulus data collected from subsurface samples [63] shows that temperature alone cannot explain the mechanical changes occurring within the reservoir, instilling the roles of compaction and alteration on strength changes.…”
Section: Impact Of Temperature On the Mechanical Properties Ofmentioning
confidence: 60%
“…However, changes in lava viscosity resulting from changing extrusion rates, increased cooling or degassing can drastically reduce the free escape of volatiles, resulting in increased explosive activity 8 . Particularly, changes in viscosity will affect the failure mode (brittle-ductile) of the dome magma and control surface strain and, in turn, the development of fractures on the dome surface 46 . Changing viscosity may also impact the mode of extrusion between endogenous and exogenous growth 47 .…”
Section: Discussionmentioning
confidence: 99%